Development and validation of the General attitude towards Medication Questionnaire (GAMQ) - Kaya J. Peerdeman; Judith Tekampe; Henriët van Middendorp; Antoinette I. M. van Laarhoven; Ralph C. A. Rippe; Madelon L. Peters; Andrea W. M. Evers (BMC Psychology, 2024)
Abstract Background Attitudes towards medication can affect treatment outcomes and adherence through mechanisms such as placebo and nocebo effects. Questionnaires assessing both negative and positive attitudes towards medication in general, which can be used across a variety of settings and in both patient and non-patient samples, are however lacking. To fill this gap, we developed and validated the General Attitude towards Medication Questionnaire (GAMQ). Methods Items were selected and adapted from existing questionnaires by a group of experts. Validation of the original Dutch version took place in 4 samples: 2 recruited from the general population (n = 508; n = 279) and 2 patient samples (patients with rheumatoid arthritis, n = 121; patients with atopic dermatitis, n = 70). We evaluated the psychometric properties of the GAMQ by determining the factor structure and its stability across samples, internal consistency, and convergent validity. Results The GAMQ contains 6 positive and 6 negatively worded items. A factor structure was observed with three subscales, representing ‘Trust in medication’, ‘Concerns about medication’, and ‘Reluctance to use medication’. The fit of the factor structure was satisfactory across samples, considering classic cut-offs, with an adequate or close to adequate fit. The total scale showed good internal consistency, good convergent validity with related scales (i.e., Beliefs about Medicines Questionnaire - General and a single medication attitude scale), and concurrent validity as reflected in associations with expectations about pain- and itch-relieving medication. It was not consistently or strongly associated with demographic or health-related characteristics. Conclusions The newly developed GAMQ showed satisfactory psychometric properties in a variety of populations, although limitations should be considered. The GAMQ is the first scale to assess both positive and negative attitudes towards medication in general, providing indicators of Trust, Concerns, and Reluctance regarding medication. The scale may be an informative measure for predicting treatment outcomes and adherence, as well as placebo and nocebo effects in diverse samples.